Regulation of electrical activity and neuronal excitability in Helisoma trivolvis by carbon monoxide. (17th December 2015) - Estes, S.; Zhong, L.R.; Artinian, L.; Rehder, V.
Graphical abstract: Highlights: Neurons from the snail, Helisoma trivolvis, were studied in cell culture. CO modulation of electrical activity and excitability was investigated. CO hyperpolarized the membrane potential and decreased neuronal excitability. CO inhibited persistent sodium current and voltage-gated calcium currents. Abstract: Carbon monoxide (CO), like other gaseous neuromodulators, has a dual nature as both a toxic gas and a physiologically relevant signaling molecule. In the nervous system, high concentrations of CO can lead to neuronal injury while lower concentrations are found to be neuroprotective. The number of cellular targets affected by physiological concentrations of CO is rapidly growing and includes ion channels in various cell types. The modulation of ion channels by CO in neurons, however, and the effect it has on neural activity are incompletely understood. Here, the well-characterized buccal neurons, B5 and B19, of the freshwater snail, Helisoma trivolvis, were used to investigate the role that CO plays in regulating spontaneous firing activity and neuronal excitability. Neurons were studied in single-cell culture, thereby removing other signals normally present in the intact nervous system and allowing for the optimal characterization of physiological effects of CO. We found that the CO donor molecule, carbon monoxide releasing molecule-2 (CORM-2), hyperpolarized the resting membrane potential of B5 neurons and silenced their spontaneous firing activity. These effects were mediated through the inhibition of a persistent sodium current. CORM-2 also inhibited neuronal excitability. This effect was mediated by the inhibition of voltage-gated calcium channels by CO. The general findings of CO acting as a hyperpolarizing signal and an inhibitor of neuronal excitability extended to B19 neurons. Taken together, these findings suggest that CO is a potent modulator of ion channels with broad implications for the modulation of neural activity in a wide range of neuron-types.